Bacterial Cyclodipeptides Target Signal Pathways Involved in Malignant Melanoma - Durán-Maldonado, Mayra Xóchitl; Hernández-Padilla, Laura; Gallardo-Pérez, Juan Carlos; Díaz-Pérez, Alma Laura; Martínez-Alcantar, Lorena; Reyes De la Cruz, Homero; Rodríguez-Zavala, José Salud; Pacheco-Rodríguez, Gustavo; Moss, Joel; Campos-García, Jesús (Frontiers in Oncology, 2020)
Melanoma is an aggressive cancer that utilizes multiple signaling pathways, including those that involve oncogenes, proto-oncogenes and tumor suppressors. It has been suggested that melanoma formation requires cross-talk of the PI3K/Akt/mTOR and Ras-ERK pathways. This pathway cross-talk has been associated with aggressiveness, drug resistance, and metastasis; thus, simultaneous targeting of components of the different pathways involved in melanoma may aid in therapy. We have previously reported that bacterial cyclodipeptides (CDPs) are cytotoxic to HeLa cells and inhibit Akt phosphorylation. Here, we show that CDPs decreased melanoma size and tumor formation in a subcutaneous xenografted mouse melanoma model. In fact, CDPs accelerated death of B16-F0 murine melanoma cells. In mice, anti-tumor effect was improved by treatment with CDPs using cyclodextrins as drug vehicle. In tumors, CDPs caused nuclear fragmentation and changed the expression of the Bcl-2 and Ki67 apoptotic markers, and promoted restoration of hyperactivation of the PI3K/Akt/mTOR pathway. Additionally, elements of several signaling pathways such as the Ras-ERK, PI3K/JNK/PKA, p27Kip1/CDK1/survivin, MAPK, HIF-1, epithelial-mesenchymal transition, and cancer stem cell pathways were also modified by treatment of xenografted melanoma mice with CDPs. The findings indicate that the multiple signaling pathways implicated in aggressiveness of the murine B16-F0 melanoma line are targeted by the bacterial CDPs. Molecular modeling of CDPs with protein kinases involved in neoplastic processes suggested that these compounds could indeed interact with the active site of the enzymes. The results suggest that CDPs may be considered as potential anti-neoplastic drugs, interfering with multiple pathways involved in tumor formation and progression.